2018
DOI: 10.1038/s41541-018-0057-5
|View full text |Cite
|
Sign up to set email alerts
|

The TLR-4 agonist adjuvant, GLA-SE, improves magnitude and quality of immune responses elicited by the ID93 tuberculosis vaccine: first-in-human trial

Abstract: Tuberculosis (TB) is the leading cause of infectious death worldwide. Development of improved TB vaccines that boost or replace BCG is a major global health goal. ID93 + GLA-SE is a fusion protein TB vaccine candidate combined with the Toll-like Receptor 4 agonist adjuvant, GLA-SE. We conducted a phase 1, randomized, double-blind, dose-escalation clinical trial to evaluate two dose levels of the ID93 antigen, administered intramuscularly alone or in combination with two dose levels of the GLA-SE adjuvant, in 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(123 citation statements)
references
References 51 publications
(54 reference statements)
4
119
0
Order By: Relevance
“…Full-length MSP1 in combination with GLA-SE is safe Between April 2017 and November 2018, 32 healthy volunteers (19 females) were recruited in a double-blind dose-escalation, placebo, and adjuvant-controlled first-in-human phase 1 clinical trial to assess the safety and immunogenicity of SumayaVAC-1, a combination of full-length MSP1 and GLA-SE as adjuvant. GLA-SE is a stable oil-in-water nanoemulsion of the TLR4 agonist glucopyranosyl lipid A. GLA-SE was chosen as an adjuvant due to its favorable safety record [54][55][56] and because it stimulates Th1 CD4 + T-cell responses to co-administered antigens, 57 a feature we consider important since CD4 + T-cells contribute via their helper and effector functions to protective immunity to blood stage malaria infection. 58 None of the volunteers had a known prior malaria infection or had been vaccinated against malaria before.…”
Section: Resultsmentioning
confidence: 99%
“…Full-length MSP1 in combination with GLA-SE is safe Between April 2017 and November 2018, 32 healthy volunteers (19 females) were recruited in a double-blind dose-escalation, placebo, and adjuvant-controlled first-in-human phase 1 clinical trial to assess the safety and immunogenicity of SumayaVAC-1, a combination of full-length MSP1 and GLA-SE as adjuvant. GLA-SE is a stable oil-in-water nanoemulsion of the TLR4 agonist glucopyranosyl lipid A. GLA-SE was chosen as an adjuvant due to its favorable safety record [54][55][56] and because it stimulates Th1 CD4 + T-cell responses to co-administered antigens, 57 a feature we consider important since CD4 + T-cells contribute via their helper and effector functions to protective immunity to blood stage malaria infection. 58 None of the volunteers had a known prior malaria infection or had been vaccinated against malaria before.…”
Section: Resultsmentioning
confidence: 99%
“…However, after 12 weeks postinfection, compared with NG-Ag85A-immunized mice, G-Ag85A immunized mice showed mild lung inflammation and limited bacterial burden in lung tissues. Although a clear protective correlation has not been fully proven, the multifunctional Th1 T cell response has been shown to be associated with protection against Mtb infection in mouse models [58][59][60]. In addition, a continuous decrease in the multifunctionality of T cells has been correlated with a decrease in the protection against Mtb infection in a mouse model [45].…”
Section: Discussionmentioning
confidence: 99%
“…The formulation of P27A in 5 µg GLA-SE is likely to induce an efficient immune response in pre-exposed populations, the target population that could benefit from the vaccine. This formulation may also be suitable for unexposed travelers since recent trials showed that 2 or 5 µg GLA-SE vaccine formulations were similarly safe (23,24). Further studies to formally confirm these observations should be performed in phase 2a and 2b clinical trials covering a greater number of volunteers.…”
Section: Discussionmentioning
confidence: 99%